DEVELOPMENT OF SHARIA BANK IN MUSLIM COUNTRIES: PERKEMBANGAN BANK SYARIAH DI NEGARA MUSLIM - Amonius Gea (LPPM UPMI, 2023)
Utilization of mutation induction or artificial mutation is one of the breeding techniques used in improving plant characteristics, such as increasing plant genetic diversity, increasing production, accelerating harvest age, and resistance to pests and diseases. This study uses the RAL method (Complete Randomized Design) consisting of 3 factors and 3 levels, namely Factor I AGNPS-A Administration at the level of Z0 = Control, Z1 = 2 MST, Z2 = 5 MST; Factor II Diethyl Sulfate Concentration at the level of S0 = Control, S1 = 0.05%, S2 = 1% and Factor III Immersion Duration at the level of J1 = 8 Hours and J2 = 16 Hours. The results showed that the single effect of AGNPS-A was significantly different on plant height at the age of 2 weeks, 3 weeks, 4 weeks, and 5 weeks, number of leaves, number of tillers, number of tubers, wet weight of tubers and dry weight of tubers; the single effect of diethyl sulfate concentration was significantly different on plant height at the age of 2 weeks, 3 weeks, 4 weeks, and 5 weeks, number of leaves, number of tillers, number of tubers, wet weight of tubers and dry weight of tubers. The interaction effect of AGNPS-A, diethyl sulfate concentration and soaking time was significantly different on plant height at the age of 2 weeks, 3 weeks, 4 weeks, and 5 weeks, number of tubers, wet weight of tubers, but not significantly different on the number of leaves, number of tillers and wet weight of tubers.